Educação: transformação ou reprodução - Francisco, Viviane Colácio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Among the various school functions in capitalist society there in the literature and common sense that the school would have a central role in correcting social inequalities produced by the capitalist mode of production. We see, in today's society, children and young people who moved by the desire to get out of where they are, usually on the outskirts, in a vulnerable situation, seek growth through the study; They see it as a way out to another reality with more opportunit ies and chances for improvement, both as regards their quality of life, and even want to change, change and influence their own reality or part of it, with the knowledge learned in school. On the other hand, there are theorists who maintain that the school reproduces the basic features of the social structure and the current system of power in society. Our goal is to discuss the transformative potential of education as opposed to its role of reproduction of social inequalities, through the essential role of the teacher, who has a high profile role when it comes to change. The teacher is one of the first professionals that we remember when we turn to the school and refer to the systematic teaching. But sometimes forms of education present in the school, afflicting much of children and young people and are characterized in order to favor certain classes and eventually stop the growth and development of those who do not meet the required standards. In this paper we intend to compare two lines of thought, alluding to pedagogical activities in class, the Paulo Freire, which brings the teacher's figure with a responsible actor for lead students to reflection of their practice; and Pierre Bourdieu, which considers the pedagogical practice as an act of imposition of values of the ruling class. The work will address the issue from literature

Dentre as várias funções da escola na sociedade capitalista há na literatura especializada e no senso comum a ideia de que a escola teria um papel central na correção das desigualdades sociais produzidas pelo modo de produção capitalista. Vemos, na sociedade atual, crianças e jovens, que movidos pela vontade de sair de onde estão, geralmente nas periferias, em situação de precariedade, buscam crescimento através do estudo; vêem nele uma saida para uma outra realidade com mais oportunidades e chances de melhora, tanto no que se refere a sua qualidade de vida, e até mesmo querer alterar, mudar e influenciar sua própria realidade ou parte dela, com o conhecimento que aprendeu na escola. Por outro lado, há teóricos que sustentam que a escola reproduz as características básicas da estrutura social e o sistema de poder vigente na sociedade. Nosso objetivo é discutir o potencial transformador da educação em contraponto ao seu papel de reprodução das desigualdades sociais, mediante a atuação imprescindível do professor, que possui um papel de grande destaque quando se trata de mudança. O professor é um dos primeiros profissionais que nos lembramos quando nos voltamos para a escola e nos referimos ao ensino sistematizado. Porém, algumas vezes, as formas de ensino presentes na escola, afligem boa parte das crianças e jovens e se caracterizam de forma a privilegiar determinadas classes, acabando por barrar o crescimento e desenvolvimento daqueles que não se enquadram nos padrãos exigidos. Neste trabalho pretendemos comparar duas linhas de pensamento, alusivas a atuação pedagógica em sala, a de Paulo Freire, que traz a figura do professor com um ator responsável por levar os alunos à reflexão de sua prática; e Pierre Bourdieu, que considera a prática pedagógica como um ato de imposição de valores da classe dominante. O trabalho abordará a questão a partir de pesquisa bibliográfica
Keywords: Freire, Paulo, 1921-1997; Bourdieu, Pierre, 1930-2002; Educação; Educação - Reprodução; Pesquisa bibliografica